THE IMPLEMENTATION OF VOCABULARY BUILDING STRATEGY IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Syafrizal, Syafrizal; Haerudin, Haerudin (Journal of English Language Teaching, 2018)
Vocabulary as one of English component and it’s very important to learn. Before the students master the four skills they have to know some vocabularies to support them in learning English. English vocabulary as one of the language skill elements has an important role for young learners in learning foreign languages. In presenting English, especially vocabulary, the teacher should be creative in choosing materials and able to stimulate the student's interest. The teacher needs to manipulate some strategies to support the teaching and learning process. Teaching English for young learner is different from teaching adults in a way that they are often more enthusiastic, active and easily adaptive than adults. The type of this research is descriptive qualitative research. This research is a descriptive qualitative research that focuses on vocabulary building strategy in teaching vocabulary to young learners. It describes the technique and method used by the teacher in teaching English vocabulary to young learner.